The concept of law / by H.L.A. Hart. - Hart, H. L. A. (Herbert Lionel Adolphus), 1907-1992 (Clarendon law series., 2012)
'The Concept of Law' is still the starting point for the study of legal philosophy and is widely heralded as a classic work of modern philosophy. This third edition features a new introduction by Leslie Green, looking at Hart's work from the perspective of modern jurisprudence.